Effect of Postharvest Application of Edible Coatings and Packaging on Acid Lime Fruit var. SunKagati 1 Quality at Ambient Storage Condition - Poudel, Sujata; Gautam, Ishwori Prasad; Khatiwada, Purushottam Prasad; Ghimire, Dipendra; Subedi, Sujan; Pandey, Suprabha; Dhakal, Mira; Regmi, Rajendra (Nepalese Horticulture, 2021)
Sunkagati-1 is one of the commonly grown acid limes recommended for terai region of Nepal with main season production from Shrawan to Poush. In recent year, area of acid lime is increasing while no appropriate technology of postharvest is available for it. An experiment was carried out with an objective to assess the influence of edible oil coatings and packaging on storage life of acid lime fruit. Fruits were harvested at physiologically mature stage with smooth and shiny appearance and treated with four edible oils (coconut oil, mustard oil, sesamum oil and castor oil), liquid paraffin 10% wax emulsion and 25 micron low density polyethylene (LDPE) packaging. The study was conducted in completely randomized block design (CRD) with seven treatments and three replications. Fruits were kept at ambient condition (20±1.55 ºC, 65±6.5 % RH) till 24 days and analyzed for various postharvest physical, chemical and physiological parameters after 8th, 16th and 24th days of storage. The result showed that LDPE packaging has significant effect on reduction of physiological loss in weight (1.69 %), spoilage loss (5.17 %), higher vitamin C content (60.11 mg/100g), Titratable acidity (6.71 %) and development of marketable color viz., 100% yellow color. Also, coconut oil showed significantly better postharvest quality retention with reduced physiological loss in weight (10.83 %) and spoilage loss (10.45 %). This study concluded that LDPE packaging and coconut oil coating are the appropriate method to extend the storage life of acid lime in ambient condition of mid hills situation.